Detecting "Faking good" with the Adolescent Substance Abuse Subtle Screening Inventory-SASSI-A3: A Clinical Response to Alcohol & Other Drug Use Minimization among Teens. Issue 3 (2nd July 2020) - Tiburcio, Nelson J.; Baker, Scarlett L.; Hanauer, Matthew
ABSTRACT: This article reviews one aspect of the clinical findings of a "fake-good data set" of the SASSI Institute's forthcoming third iteration of the Adolescent Substance Abuse Subtle Screening Inventory (SASSI-A3). We are evaluating new items for inclusion in the SASSI-A3 to address emerging issues and contemporary trends; comparison of honest and "fake" responses from participants with known Substance Use Disorders (SUDs), and in order to validate the instrument's efficacy identifying likely SUD profiles when respondents do not fully acknowledge substance misuse. Such respondent drug use pattern minimization is known as "faking-good." This is the first in a series of reports comprising a validation study by the SASSI Institute to monitor the concordance and accuracy of the adolescent SASSI substance use screening measure against DSM-5 criteria for diagnosing SUDs. Providing screening and assessment professionals appropriate scale scores to identify defensive client responses, or attempts to minimize disclosure of substance abuse, can inform subsequent clinical interviews. These scale scores will assist professionals with treatment planning, enhancing treatment placement and related conditions.